A Systematic Review of Threshold Concepts in Higher Education: Characteristics, Learning Barriers, and Pedagogical Interventions - Firdaus, Laras; Dewi, Ika Nurani; Primawati, Sri Nopita; Hulyadi, Hulyadi; Sabrun, Sabrun; Azmi, Irham (International Journal of Essential Competencies in Education, 2025)
This systematic review synthesises peer-reviewed empirical and conceptual research on threshold concepts (TC) in higher education published between 2015 and 2025. The review aims to examine how threshold concepts are theorised, operationalised, and empirically investigated across disciplinary contexts, with particular attention to their defining characteristics, associated learning difficulties, and pedagogical implications. Following a rigorous process of database searching, screening, and eligibility assessment, a total of 26 studies were included, comprising 11 peer-reviewed journal articles and 15 articles reporting empirical studies. The analysis integrates qualitative, quantitative, and mixed-methods studies to generate three key contributions: (1) a refined synthesis of TC characteristics as epistemic and, in some cases, ontological turning points in learning; (2) a structured categorisation of learning challenges associated with threshold crossing, including cognitive, affective, and contextual dimensions; and (3) an overview of pedagogical approaches designed to support learners during liminal phases. Findings indicate that TC consistently facilitate transitions from surface understanding to disciplinary ways of knowing, although their forms and manifestations vary across fields. While pedagogical interventions increasingly acknowledge the necessity of learning difficulty, robust longitudinal evidence remains limited. The review concludes with practical indicators for educators, and methodological recommendations, especially the need for longitudinal study, mixed methods design, and clearer operational criteria to strengthen future research and curriculum design.